Thanks, Tshepo! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Álvaro Soares de Melo, formerly responsible for Spore s Portuguese-language sister publication Esporo, has some words of thanks for Ms Tshepo Khumbane of South Africa and her Viewpoint 'Subsistence lives' in Spore 91/Esporo 41. 'Congratulations...